Frameworks for sustainable development goals to manage economic, social, and environmental shocks and disasters - Popescu, Cristina Raluca Gh., 1983- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This book provides valuable insight of today's context concerning the creation of an international successful framework for Sustainable Development Goals (SDGs) that requires managing the economic, social and environmental shocks and disasters in the Post-COVID-19 Era"--